2022
DOI: 10.1186/s40317-022-00307-w
|View full text |Cite
|
Sign up to set email alerts
|

WATLAS: high-throughput and real-time tracking of many small birds in the Dutch Wadden Sea

Abstract: Tracking animal movement is important for understanding how animals interact with their (changing) environment, and crucial for predicting and explaining how animals are affected by anthropogenic activities. The Wadden Sea is a UNESCO World Heritage Site and a region of global importance for millions of shorebirds. Due to climate change and anthropogenic activity, understanding and predicting movement and space-use in areas like the Wadden Sea is increasingly important. Monitoring and predicting animal movemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Former studies have shown that red knots in the Wadden Sea are highly mobile and may switch between foraging sites and high tide roosts, respectively, in short periods of time (42, 43). In addition, virological investigations confirmed viral loads in oropharyngeal and cloacal samples suggesting virus shedding and transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have shown that red knots in the Wadden Sea are highly mobile and may switch between foraging sites and high tide roosts, respectively, in short periods of time (42, 43). In addition, virological investigations confirmed viral loads in oropharyngeal and cloacal samples suggesting virus shedding and transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We caught red knots using mist‐nets on the Griend and Richel mudflats in the Wadden Sea, the Netherlands (53°15′ N, 5°15′ E), between July and October in 2019 ( n = 251) and 2020 ( n = 244). We equipped them with lightweight ATLAS tags (4.4 g, ~3.4% of their body mass), which we tracked with a high‐resolution regional‐scale reverse‐GPS tracking system (Beardsworth et al., 2022 ; Bijleveld et al., 2022 ; Weiser et al., 2016 ). The Wadden Sea ATLAS (WATLAS) tracking area is approximately 1400 km 2 comprising a total of 26 receiver stations (Data S1 ) (Beardsworth et al., 2022 , Bijleveld et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…We equipped them with lightweight ATLAS tags (4.4 g, ~3.4% of their body mass), which we tracked with a high‐resolution regional‐scale reverse‐GPS tracking system (Beardsworth et al., 2022 ; Bijleveld et al., 2022 ; Weiser et al., 2016 ). The Wadden Sea ATLAS (WATLAS) tracking area is approximately 1400 km 2 comprising a total of 26 receiver stations (Data S1 ) (Beardsworth et al., 2022 , Bijleveld et al., 2022 ). Tags emit a radio signal at 434 MHz and if at least three receiver stations detect the transmission, the system can calculate a location based on the transmission time of arrival.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATLAS has proven to be a maintainable and productive regional high-throughput wildlife tracking system. It can track many species of wild animals at high temporal and spatial resolution using ToA radio transmitter localization [3,4,[12][13][14]. Six separate ATLAS systems, each consisting of 5 to 25 receivers, in four countries have tracked over 7000 transmitters, called tags, over the past 8 years, and a few more systems are under construction.…”
Section: Atlasmentioning
confidence: 99%